1992
DOI: 10.1093/nar/20.14.3725
|View full text |Cite
|
Sign up to set email alerts
|

ThePCF1–1mutation increases the activity of the transcription factor (TF) IIIB fraction fromSaccharomyces cerevisae

Abstract: PCF1-1 is a dominant suppressor of a tRNA gene A block promoter mutation (A19) in Saccharomyces cerevisiae. Transcriptional activation by PCF1-1 was examined in vitro using whole-cell extracts and purified factors derived from mutant and wild-type strains. These experiments show that PCF1 is a general activator of RNA polymerase III (pol III) gene transcription. The transcription of all pol III genes analyzed to date, including type I and numerous type II genes, is increased 3-7 fold in mutant cell extracts. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The biochemical basis of the PCFI-l rate effect is currently under investigation. In addition to increasing the rate of preinitiation complex assembly, single-round initiation assays have demonstrated that the PCFJ-1 mutation also increases the number of transcriptionally active complexes in crude cell extracts (38). Our present findings that TFIIIB fractions purified from mutant cells contain more TFIIIB70 and have elevated TFIIIB" activity suggest that these observations are related.…”
Section: Tfiiib90supporting
confidence: 49%
See 3 more Smart Citations
“…The biochemical basis of the PCFI-l rate effect is currently under investigation. In addition to increasing the rate of preinitiation complex assembly, single-round initiation assays have demonstrated that the PCFJ-1 mutation also increases the number of transcriptionally active complexes in crude cell extracts (38). Our present findings that TFIIIB fractions purified from mutant cells contain more TFIIIB70 and have elevated TFIIIB" activity suggest that these observations are related.…”
Section: Tfiiib90supporting
confidence: 49%
“…7, lanes 4 and 5). With recombinant TBP as a standard, both fractions were found to contain a significant molar excess (about 100-fold for the mutant TFIIIB fraction) of TBP polypeptide relative to TFIIIB (based on activity measurements [30] cell extracts is reduced from about six-to threefold (38,39).…”
Section: Tfiiib90mentioning
confidence: 99%
See 2 more Smart Citations
“…One intriguing idea is that the TFIIIB factor, which binds immediately upstream of the pol III transcription initiation site, might be inhibiting pol II transcription by serving as a competitive ligand for components of the pol II transcription machinery. TFIIIB is composed of several subunits, including the TATA-binding protein (3,40,50,53,66,67,92,103,104). If this factor, or any other component of the pol III complex (7,9,17,19,21,48,51,63,91,105), bound tightly to the activation domains of factors bound at the UAS elements, interactions with the pol II basal promoter complex could be competed for (Fig.…”
Section: Resultsmentioning
confidence: 99%